Antifungal activity of ethanolic extract of Sphaeranthus indicus Linn. against Dermatophytes and Candida species - Sundaresan, Preeja K.; Kesavan, Kala P. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Sphaeranthus indicus as an entire plant or the specific parts like roots, leaves, flowers are used for treating helminthiasis, jaundice, diabetes, dyspepsia, fever, cough, hernia, gastritis, hemorrhoids, migraine, leprosy and skin diseases. The objective of this study was to evaluate the antifungal activity of ethanolic extract of the whole plant Sphaeranthus indicus Linn. Methods: The antifungal activity of ethanolic extract of the whole plant Sphaeranthus indicus Linn was evaluated by incorporating the extract in Sabourauds dextrose agar. This property was studied in vitro using the ethanolic extract on Candida albicans, Microsporum gypseum, Trichophyton mentagrophytes and Epidermophyton floccosum by using Clotrimazole as standard drug. Results: This study revealed that the ethanolic extract of Sphaeranthus indicus is having good antifungal activity against Dermatophytes and Candida species. Conclusions: This study demonstrates the promising antifungal action of ethanolic extract of whole plant of Sphaeranthus indicus Linn. This feature can be exploited in the development of a newer antifungal agent from plant.